2016
DOI: 10.2500/ajra.2016.30.4316
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Depot House-Dust Mite Allergen Extract for Chinese with Allergic Rhinitis and Asthma

Abstract: HDM-SCIT was safe and effective in the treatment of allergic rhinitis and asthma in a Chinese population, with good compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…However, one recent study in China has demonstrated good tolerance and safety of SLIT in children as young as 3 years old with Der f-induced AR with or without asthma (54). Similarly, another study has reported good tolerance and safety of HDM-SCIT in over 5 years-old children with a history of HDM-induced AR or asthma (47).…”
Section: Special Considerations In Childrenmentioning
confidence: 99%
See 3 more Smart Citations
“…However, one recent study in China has demonstrated good tolerance and safety of SLIT in children as young as 3 years old with Der f-induced AR with or without asthma (54). Similarly, another study has reported good tolerance and safety of HDM-SCIT in over 5 years-old children with a history of HDM-induced AR or asthma (47).…”
Section: Special Considerations In Childrenmentioning
confidence: 99%
“…AIT can prolong symptoms remission after discontinuation of treatment in children with AR (42)(43)(44)(45)(46)(47)(48). Significantly lower symptom scores and better quality of life scores were found in children treated with SCIT for 3 years, compared with either baseline scores or in children treated with conventional medication (42).…”
Section: Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…The study performed by Frendø et al 9 showed the high frequency of asthma in patients with CRS, and, much like the study by Dogru, 5 indicated a need for upper-airway physicians to be cognizant and investigate for the presence of lower airway disorder. Xiang et al 10 evaluated the role for house-dust mite allergen extract subcutaneous immunotherapy and its response in China. They found very good safety and effectiveness in the treatment of both AR and asthma, and that, along with other medical approaches, immunotherapy should be considered.…”
mentioning
confidence: 99%